The effect of Tabata-style training on some functional indicators and physical abilities of 200-meter runners - Abdulwahid, Asst. Prof. Dr. Bashayer Hashem; Hassoun, Prof. Dr. Rami Abdul-Amir; Hamza, Prof. Dr. Haider Abdul Ali (Sulaimani Journal for Humanities, 2026)
The 200-meter race is considered one of the games that requires great physical fitness and movement in order for the competitor to complete the race with high efficiency without a clear drop in level, especially at the end of the race, as the 200-meter race is one of the events that depend on the lactic energy system, and this requires great effort from the player and the coach, and as it is one of the events that require a great deal of speed endurance, this causes a great accumulation of lactic acid levels in the muscle, which in turn causes great fatigue for the competitor, especially the running steps in the last third of the race. Therefore, the research study aimed to prepare training with anaerobic lactic effort in the Tabata style in order to develop some functional indicators and speed endurance for 200-meter competitors. The research population consisted of six young 200-meter runners from Al-Ghadiriya and Al-Iraq clubs in Karbala Governorate for the 2024 season. These runners were divided equally into two groups: a control group and an experimental group. The research sample was selected using a census method. The training period was eight weeks, with three sessions per week, totaling 24 training sessions. The training method used was high-intensity interval training (HIIT) using the Tabata technique. Each session consisted of approximately half an hour of the main training time, with the athletes completing the remaining time with the coach's instructions, maintaining the intensity of the Tabata exercises. The most important conclusion reached by the researchers was that the Tabata technique led to improved muscle adaptation, enabling the runners to tolerate higher lactic acid concentrations and LDH enzyme activity in the blood. Furthermore, the training methods contributed to an increase in the maximum anaerobic capacity of the experimental group, which in turn enhanced their speed endurance.
Keywords: Tabata; Biochemical Indicators; Speed Endurance